2020
DOI: 10.1177/1362168820958400
|View full text |Cite
|
Sign up to set email alerts
|

Language mindsets, perceived instrumentality, engagement and graded performance in English as a foreign language students

Abstract: This study aimed to examine the relationships between English as a foreign language (EFL) students’ language mindsets (i.e. entity and incremental beliefs about general language intelligence, second language aptitude, and age sensitivity in language learning) and graded performance by considering the mediating roles of their perceived instrumentality as well as four aspects of engagement (i.e. agentic engagement, behavioral engagement, emotional engagement, and cognitive engagement) within English classes. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 77 publications
5
14
0
Order By: Relevance
“…Based on the findings, it can be inferred that when learners engage in foreign language classroom activities and put effort into language learning, they are more likely to score high on tests. This outcome supports those results that L2 engagement, whether it was treated as a multidimensional concept or a single dimension, had a positive and predictive impact on L2 achievement ( Masgoret and Gardner, 2003 ; Eren and Rakıcıoğlu-Söylemez, 2020 ; Khajavy, 2021 ; Feng and Hong, 2022 ; Kang and Wu, 2022 ). From a broader perspective, the role of engagement as a critical contributor to learning and academic success was further confirmed, corroborating the findings of the existing literature ( Klem and Connell, 2004 ; Reeve and Lee, 2014 ; Wang and Fredricks, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the findings, it can be inferred that when learners engage in foreign language classroom activities and put effort into language learning, they are more likely to score high on tests. This outcome supports those results that L2 engagement, whether it was treated as a multidimensional concept or a single dimension, had a positive and predictive impact on L2 achievement ( Masgoret and Gardner, 2003 ; Eren and Rakıcıoğlu-Söylemez, 2020 ; Khajavy, 2021 ; Feng and Hong, 2022 ; Kang and Wu, 2022 ). From a broader perspective, the role of engagement as a critical contributor to learning and academic success was further confirmed, corroborating the findings of the existing literature ( Klem and Connell, 2004 ; Reeve and Lee, 2014 ; Wang and Fredricks, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
“…L2 engagement is defined as the extent to which a language learner is involved in doing a language learning task ( Hiver et al, 2021b ). Studies have connected engagement to foreign language classroom environment ( Sulis and Philp, 2021 ; Mohammad Hosseini et al, 2022 ), learning and communication mode ( Carver et al, 2021 ), learner-related variables ( Mercer and Dörnyei, 2020 ; Dewale and Li, 2021 ; Guo, 2021 ; Derakhshan et al, 2022 ; Zhao and Yang, 2022 ), and foreign language achievement ( Masgoret and Gardner, 2003 ; Eren and Rakıcıoğlu-Söylemez, 2020 ; Kang and Wu, 2022 ). Nevertheless, the sources and effects of this important construct in foreign language learning still have not been explicated in depth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, learners with a strong growth mindset could counter hurdles and react positively to failures than learners with a strong fixed mindset. Some studies have identified a relationship between mindsets and academic success (e.g., Mouratidis et al, 2017) whereas others failed to find any link between mindsets and success (e.g., Eren & Rakıcıog˘lu-So¨ylemez, 2023). Growth mindsets are critical for students' tenacity and long-term success (Yeager & Dweck, 2012).…”
Section: Language Mindsetsmentioning
confidence: 99%
“…As argued by Reeve and Tseng (2011), the triple model overlooked students' 10.3389/fpsyg.2022.987554 agentic involvement, and then agentic engagement was added to indicate students' constructional, proactive, and intentional contribution to their learning. The proposed four-dimension model is empirically validated in the EFL context (e.g., Eren and Rakıcıoglu-Söylemez, 2020;Guo, 2021). Based on the assumption that the true potential of students' engagement cannot be captured by a single dimension (Zhou et al, 2021), engagement in the present study was defined as a multidimensional concept, incorporating behavioral, cognitive, emotional as well as agentic aspects (Reeve, 2012).…”
Section: Academic Engagementmentioning
confidence: 99%